History and faces of orthodox islam and muslims in Nigeria (2013)
This paper provides a historical framework of reconstructing the orthodox faces of Islam in Nigeria from the time of its foothold in Kanem and Bornu kingdoms to the present modern Nigeria and contends that some basic homogeneous beliefs and features serve as a definition of .orthodox Islam in Nigeria. The paper argues further that the commonality of these beliefs and practice of Islam far outweigh the "differences and dichotomies" in the abuses and corruption of Islam. In reclaiming the true orthodox identities of Muslims in Nigeria, the paper eschews both the 'Outside-In' and 'Inside-Out' schemas that construct Islam and Muslims using a unipolar approach by either outsiders-non-Muslims or insiders- Muslims.